1967
DOI: 10.1111/j.1365-2621.1967.tb00839.x
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation and Characterization of the Tribe Mimeae in Foodstuffs

Abstract: SUMMARY— Mima and Herellea organisms, which have been reported to be members of the tribe Mimeae and to have pathogenic properties, were isolated from 25 of 96 retail food samples investigated. Mima were isolated from 16% of the samples; Herellea were found in 9%. Fresh and prepared meats, seafoods, dairy products, and vegetables contained these organisms, but dehydrated foods were free of Mimeae. Because of certain similarity to the Neisseriaceae and the pseudomonads and their relatively limited biochemical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1968
1968
1978
1978

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…the surfaces of various semisolid media. They have also been found to be present in a variety of food products (52).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the surfaces of various semisolid media. They have also been found to be present in a variety of food products (52).…”
Section: Resultsmentioning
confidence: 99%
“…Some of these organisms appear to be responsible for spontaneous abortion in many different kinds of animals (11). Acinetobacter species have also been isolated from a variety of foods (36,52,54).…”
Section: Discussionmentioning
confidence: 99%
“…Research reported under project no. 16-23. shown to be widespread, occurring in various types of unprocessed foods, e.g., dairy products (6), fish (9), and vegetables (10).…”
mentioning
confidence: 99%
“…nov. have' no presently recognized public health significance (Lewis, 197 1;Thornley, 1963). M-A have been found in a variety of food products (Koburger, 1964;Shewan, 197 1;Snodgrass and Koburger, 1967) without being associated with spoilage, except in marine fish and shellfish (Herbert et al,197 1). However, M-A have been associated with both human and animal infections (Henriksen, 1973).…”
Section: Introductionmentioning
confidence: 99%